2017
DOI: 10.1038/srep39936
|View full text |Cite
|
Sign up to set email alerts
|

Very Early Colorectal Anastomotic Leakage within 5 Post-operative Days: a More Severe Subtype Needs Relaparatomy

Abstract: Early anastomotic leakage (AL), usually defined as leakage within 30 post-operative days, represents a severe entity. However, mounting evidence has indicated that majorities of leakage occur within one week after surgery, making late AL rarity. Here we analyzed 101 consecutive colorectal AL, all of which occurred within 30 post-operative days, during Jan 2013 and Dec 2015 in cancer hospital of Fudan University. AL occurring within 5 post-operative days was defined as very early AL (vE-AL). We evaluated risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 27 publications
4
36
1
1
Order By: Relevance
“…8 On the other hand, Yi-Wei Li. 9 Demonstrated risk factors for AL including male sex, high American Society of Anesthesiologists (ASA) fitness grade, emergency surgery, gender is not with statistical significance in our study.…”
Section: Discussioncontrasting
confidence: 65%
“…8 On the other hand, Yi-Wei Li. 9 Demonstrated risk factors for AL including male sex, high American Society of Anesthesiologists (ASA) fitness grade, emergency surgery, gender is not with statistical significance in our study.…”
Section: Discussioncontrasting
confidence: 65%
“…In order to evaluate the postoperative appearance day of fistulas, there were separated three groups, as follows: early appearance of anastomotic leak (1-4 days), median appearance of fistula (5-10 days) and late appearance of anastomotic leakage (>30 days) (7).…”
Section: Resultsmentioning
confidence: 99%
“…There were also no clinical changes observed that would suggest development of sepsis or ileus, and the animals managed to maintain their weight; therefore we assume the material does not contribute to postoperative GI obstruction. Most patients develop an anastomotic leakage within the first 2 weeks after the surgery 45,46 , we covered three postoperative weeks of observation. www.nature.com/scientificreports www.nature.com/scientificreports/ Nordentoft et al experimented with fibrin coated collagen patches (TachoSil, fibrin sealant) in a pig model of intestinal anastomosis.…”
Section: Discussionmentioning
confidence: 99%